Avaliação das habilidades neurocognitivas em crianças e adolescentes sobreviventes da Leucemia Linfoide Aguda - LLA - Silva, Débora Sunaly Leite da (2014)
The present study investigated the impact of the treatment modalities of Acute Lymphoblastic Leukemia on neurocognitive abilities of children and adolescents survivors, aged between 6 and 16 years of age, accompanied in pediatric oncology sectors of public health services in the cities of Campina Grande-PB and Natal-RN. The study included 52 children, 13 of these being children and adolescents diagnosed with leukemia and 39 healthy children matched in relation to the study group considering gender, age, school type and level of maternal education. Later the group of children with leukemia was subdivided into two subgroups depending on treatment modality which were submitted: Group 1A (only chemotherapy) and 1B (chemotherapy and radiotherapy). All participants were subjected to a battery of neuropsychological tests that investigated the following neurocognitive abilities: intellectual ability, memory system, attention, visuospatiality and visuoconstruction, processing speed and executive functions. Data were analyzed using descriptive and inferential measurements with the aid of the U test of Mann-Whitney and T test, considering the influence of the variables: sex, age at diagnosis, time since completion of treatment and level of schooling mothers, on the performance of children. Overall, it is concluded that the illness and the treatment of acute lymphoblastic leukemia significantly favors the emergence of cognitive deficits, particularly in terms of visuospatial skills, and executive skills visoconstrutivas. In turn, the treatment modality of radiotherapy is associated with the presence of more severe deficits, highlighting the significant impact on the speed of information processing. It is hoped that the results presented here will contribute to a better understanding of the nature and extent of neurocognitive effects arising ALL treatment